2003
DOI: 10.1007/s00239-002-2395-0
|View full text |Cite
|
Sign up to set email alerts
|

Broad-Scale Analysis Contradicts the Theory That Generation Time Affects Molecular Evolutionary Rates in Plants

Abstract: Several studies of plant taxa have concluded that generation time, including annual/perennial life history, may explain molecular evolutionary rate variation in selectively neutral DNA. Unlike in animals, there is little theoretical basis for why generation-time effects would exist in plants. Furthermore, previous reports fail to establish the generality of a generation-time effect in plants because of the small size of the datasets, a large proportion of which compared very widely divergent taxa differing in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 67 publications
1
67
2
Order By: Relevance
“…As a result, generation time can provide a useful proxy of the overall rate of genome replication in animals, but is unlikely to do so in plants. This may explain why the evidence for the generation time hypothesis is very strong for animals [16][17][18] , but mixed for plants 1,[19][20][21] . Despite this, generation time will remain tightly associated with long-term rates of meiosis in plants, because an extant plant genome would have experienced one meiosis in each generation through which it has passed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, generation time can provide a useful proxy of the overall rate of genome replication in animals, but is unlikely to do so in plants. This may explain why the evidence for the generation time hypothesis is very strong for animals [16][17][18] , but mixed for plants 1,[19][20][21] . Despite this, generation time will remain tightly associated with long-term rates of meiosis in plants, because an extant plant genome would have experienced one meiosis in each generation through which it has passed.…”
Section: Discussionmentioning
confidence: 99%
“…In all three of these cases, the faster-evolving plants (annuals, herbs and non-arborescent ferns) are likely to have higher rates of mitosis than their more slowly evolving relatives (perennials, woody species and tree ferns), although we also note that the faster-evolving plants are also likely to have shorter generation times in all of these cases. The ROM hypothesis might also explain why generation times correlate with rates of molecular evolution in animals, but not in plants 20,21,36 , because generation times are a reliable predictor of rates of mitosis in animals, but not in plants. Finally, the ROM hypothesis might explain previously observed correlations between rates of molecular evolution and environmental energy 3 , latitude 2 and water availability 5 in plants.…”
Section: Article Nature Communications | Doi: 101038/ncomms2836mentioning
confidence: 99%
“…1, Table 1, and Table 6), we conclude that rate variation in Plantago mt genes is probably a direct consequence of underlying changes in the mt mutation rate. In contrast, most previously reported cases of (much more modest) synonymous site variation in plant mt DNA have been postulated to reflect generation time effects (13)(14)(15), although this interpretation has been questioned (41).…”
Section: Underlying Basis Of Extreme Molecular Divergence In Plantagomentioning
confidence: 93%
“…(Thomas et al, 2010). Although under-examined, the predicted correlation between generation time and rates of molecular evolution has been observed in some groups of invertebrates, flowering plants, host-parasite systems and mammalian nuclear sequences (Nikolaev et al, 2007;Smith and Donoghue, 2008;Welch et al, 2008;Thomas et al, 2010), but not for other plants or mammal mtDNA (Whittle and Johnston, 2003;Nabholz et al, 2008). Ohta (1992) suggested that variation in generation time and population size was the cause of the discrepancy between observed rates of protein and nucleotide evolution.…”
Section: The Process Behind the Patternmentioning
confidence: 99%